Biskuit Bebas Gluten menggunakan Bahan Baku Tepung Mocaf dan Blondo - Verawati, Nenengsih; Aida, Nur; Hartoni, Nanang (AGRITEKNO: Jurnal Teknologi Pertanian, 2025)
This study evaluated the effects of substituting modified cassava flour (mocaf) with blondo coconut oil on the moisture, fat, protein, carbohydrate, and ash content of gluten-free cookies. A completely randomized design with a one-factor arrangement was applied, consisting of five substitution levels of macaf to blondo (300:0 g; 250:50 g; 200:100 g; 150:150 g; 100:200 g). The highest moisture content (4.84%) was obtained at 100 g of mocaf and 200 g of blondo, while the lowest (4.64%) occurred with 300 g of mocaf and 0 g of blondo. The highest ash content (1.29%) was recorded at 200 g blondo, and the lowest (0.99%) was with no blondo. Protein content peaked at 4.59% (200 g of mocaf, 100 g of blondo) and was lowest at 3.88% (300 g of mocaf, 0 g of blondo). Fat content ranged from 7.83 (300 g mocaf, 0 g blondo) to 9.51% (200g mocaf, 100 g blondo), while carbohydrate content was highest at 69.24% (300 g mocaf, 0 g blondo) and lowest at 67.11% (100 g mocaf, 200 g blondo). This result demonstrates that partial substitution of mocaf with blondo significantly alters the nutritional profile of gluten-free cookies.